التكريس الدستوري للحق في بيئة سليمة كأساس لممارسة المواطنة البيئية في الجزائرla Concrétisation Du Droit à Un Environnement Sain Comme Un Fondement De La Mise En œuvre De La Citoyenneté Environnementale En Algérielegalization Of The Right To A Sound Environment As A Basis For The Exercise Of Environmental Citizenship In Algeria - محمد أمين, أوكيل (Université de M'sila, 2020)
تتناول هذه الدراسة تبيان وتحليل مسار التكريس القانوني للحق في بيئة سليمة في القانون الدولي وفي القانون الجزائري، لا سيما بعد إقراره في نص المادة 68 من الدستور مؤخرا عقب التعديل الدستوري المؤرخ في 6 مارس 2016، وذلك بالتركيز على أبعاد وآثار تكريس الحق في بيئة سليمة ودورها في تدعيم وتفعيل المواطنة البيئية. وعلى هذا الأساس سمحت لنا هذه الدراسة تبيان مفهوم المواطنة البيئية، والدور المنوط بالمواطنين ممارسته في إطارها لاسيما من خلال المشاركة في تسيير الشؤون البيئية والدفاع عن سلامتها من التهديدات المخلة بأمنها وتدهورها في إطار إعداد وتنفيذ السياسة البيئية للدولة، فضلا عن بيان الدور المكفول للدولة في تأطير وتنظيم سبل وآليات ممارسة المواطنة البيئية في الجزائر. وخلصنا في الختام إلى تحديد مجال ممارسة المواطنين لحقوق المواطنة البيئية وأهم الأدوات القانونية التي يستعملونها لتفعيل هذا المبدأ من قبيل الاستشارة العمومية والتحقيق العمومي والحق في اللجوء إلى العدالة البيئية. This study deals with the role of legalization of the right to a sound environment in the exercise of the rights and obligations of environmental citizenship in Algeria. Where we addressed the issue on the basis of the problem of demonstrating the impact of the right to an environment in activating the rights of environmental citizenship. On this basis, we divided the study into two areas. In the first, we examined and analyzed the path of legal entrenchment of the right to a sound environment within the framework of the analysis of the rules of international law, especially in international environmental conventions, declarations and covenants, or those relating to human rights as the direct basis for the emergence and development of the right to a sound environment Which was linked to human rights before it became independent and self-contained. We then examined the right to a sound environment and its development in Algerian law, starting with environmental laws such as Law 03-83 (revoked) and Law 03-10 on the protection of the environment in the framework of sustainable development, as well as other laws related to the field of environmental protection, And subsequently in the various constitutional documents, especially after its adoption in the text of Article 68 of the Constitution recently following the constitutional amendment of 6 March 2016. While we dealt in the second axis of the study dimensions and effects of the entrenchment of the right to a sound environment and its role in strengthening and activating environmental citizenship. On this basis, we first illustrated the concept of environmental citizenship and its relation to citizenship based on the analysis of the text of Article 68 of the Constitution which defines the rights and obligations of protecting the environment and the role assigned to citizens in the framework of it, in particular by participating in the conduct of environmental affairs and defending its safety from threats to its security and deterioration Preparation and implementation of the state's environmental policy, as well as the state's guaranteed role in setting general policies for the protection of the environment, framing and regulating the ways and mechanisms of practicing environmental citizenship in Algeria and defining the legal tools for protecting the environment to achieve the Laminate in the environmental field. In conclusion, we also concluded by defining the scope of citizens' exercise of the rights of environmental citizenship and the most important legal tools they use to activate this principle, such as public consultation and public inquiry and the right to resort to environmental justice. In addition to laws related to the field of environmental protection such as the laws of reconstruction and the city, which remains on the legislator the duty to consolidate mechanisms and determine the scope of practice after the issuance of the law provided for in Article 68 of the Constitution. Cette étude vise a d'analyser l'évolution de la légalisation du droit à un environnement sain en droit international et en droit algérien, en particulier après son récente adoption dans la Constitution à la suite de l'amendement constitutionnel du 6 mars 2016, en mettant l'accent sur les dimensions et les effets du droit. pour un environnement sain et son rôle dans l'activation de la citoyenneté environnementale, en démontrant le concept de cette dernière et le rôle assigné aux citoyens, notamment en participant à la conduite des affaires environnementales et en défendant leur sécurité contre les menaces pour leur sécurité et leur détérioration dans le cadre de la préparation et la mise en œuvre de la politique environnementale de l'État, ainsi que le rôle de l'État dans la définition et l'organisation des mécanismes de mise en œuvre de la citoyenneté environnementale en Algérie.
Keywords: الحق في بيئة سليمة ; المواطنة البيئية ; العدالة البيئية ; الاستشارة العمومية ; التحقيق العمومي ; right to a healthy environment ; environmental citizenship ; environmental justice ; Droit à un environnement sain; citoyenneté environnementale ; justice environnementale ; consultation publique ; enquête publique